Shikonin Induced Program Cell Death through Generation of Reactive Oxygen Species in Renal Cancer Cells - Ming-Feng Tsai; Shih-Ming Chen; Ann-Zhi Ong; Yi-Hsuan Chung; Pei-Ni Chen; Yi-Hsien Hsieh; Yu-Ting Kang; Li-Sung Hsu (MDPI AG, 2021)
Shikonin mitigated tumor cell proliferation by elevating reactive oxygen species (ROS) levels. Herein, we investigated the effects of shikonin on renal cancer cell (RCC) cell proliferation. 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay indicated that shikonin dose-dependently reduced the proliferation of Caki-1 and ACHN cells. Shikonin remarkably triggered necrosis and apoptosis in Caki-1 and ACHN cells in proportion to its concentration. Moreover, necrostatin-1 recovered cell viability in the presence of shikonin. Elevated ROS levels and mitochondrial dysfunction were also found in shikonin treatment groups. Pretreatment with N-acetyl cysteine remarkably mitigated shikonin-induced cell death and ROS generation. Western blot analysis revealed that shikonin reduced pro-PARP, pro-caspase-3, and Bcl-2 expression and increased cleavage PARP expression. Enhanced autophagy was also found in the shikonin-treated group as evidenced by acridine orange staining. Moreover, light chain 3B (LC3B)-II accumulation and enhanced p62 expression indicated that autophagy occurred in the shikonin-treated group. LC3B knockdown considerably recovered cell viability in the presence of shikonin. Shikonin treatment elevated p38 activity in a dose-dependent manner. In conclusion, our results revealed that shikonin triggered programmed cell death via the elevation of ROS level and p38 activity in different types of RCC cells. These findings suggested that shikonin may be a potential anti-RCC agent.